KARAKTERISASI ETOSOM ASAM GLIKOLAT SEBAGAI ANTIBAKTERI DENGAN VARIASI ETANOL SEBAGAI PEMBENTUK VESIKEL - Novi Nurleni; Arie Firdiawan (Jurnal Farmasi Indonesia, 2025)
Glycolic acid has antibacterial properties and is hydrophilic which makes it difficult to penetrate through skin lipids to reach target cells. Thus, it is necessary to develop a delivery system in the form of ethosomes containing glycolic acid to increase drug penetration. The method used was hot preparation by varying ethanol concentrations of 20, 30 and 40% as vesicle formers with observations of organoleptics, homogeneity, pH, viscosity, flow properties and cyling tests. The results obtained with the variation of ethanol concentration can affect the characterization of glycolic acid ethosomes. However, no significant changes occurred during 28 days storage (p>0.005).